PENDIDIKAN KEWARGANEGARAAN DAN PANCASILA UNTUK MEMBANGUN KARAKTER BANGSA INDONESIA DI UNIVERSITAS PGRI PALEMBANG PROVINSI SUMATERA SELATAN (PROSPEK DAN TANTANGAN BAGI MAHASISWA UNIVERSITAS PGRI PALEMBANG) - Herlina, Ning (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
The course of Citizenship Education has vision, mission, goals and competence in universities is a source of values and guidance in the development and implementation of study programs to deliver students to solidify their personality as a whole Indonesian man and nurture noble humanitarian character. The mission of civic education in college helps students to strengthen their personality to be consistently capable of realizing the basic values of Pancasila, the sense of nationality and love of the homeland throughout life in mastering, applying and developing the science of technology and art that it possesses with a sense of responsibility and firmly hold unity and the unity of the nation and state.